A case study on the bedroom spaces of selected postpartum mothers in low-income households in Krus na Ligas, Quezon City - De Jesus, Patricia Bernadette S.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This case study analyzed the physical conditions of the bedroom spaces or sleeping areas of ten postpartum mothers from low-income households. Through purposive sampling, the respondents were selected through a health center in Brgy. Krus na Ligas, Quezon City. The data gathering included site observation and walk-through of the homes of selected respondents; and interviews among the postpartum mothers and a health care professional. The data were tabulated, coded, and cross-referenced to highlight themes and issues. The interior conditions of the homes of the respondents generally showed good sanitation, use of natural ventilation trough large windows and effective use of makeshift storage systems. External factors such as noise and dust negatively affected the respondents' living conditions. Health, home environment, socioeconimic status, and external environment were observed as key factors that affected their experiences in the home during postpartum recovery and childrearing. Mothers who lived in units with shared sleeping spaces with other family members had limited privacy and comfort. However, the sharing of sleeping spaces with other family members was not viewed to have a negative effect for postpartum mothers since social support from family members and neighbors has become one of the coping strategies of postpartum mothers. Bed sharing with infants also provided security for mothers when tending to their infant's needs. The findings of this study may aid in supporting the needs of postpartum mothers in their sleeping spaces from low-income households.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Bedrooms -- Philippines -- Kruz na Ligas (Quezon City)